Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Gojek Wilayah Jakarta - Erlinda Nafisah Hanan; Dika Ariska Silviana; Fariz Maulana Noorend; Muhammad Abdullah (Jurnal Manajemen Dirgantara, 2024)
This study aims to elucidate the relationships and impacts between independent and dependent variables within the context of online transportation services, which have gained significant relevance in the digital age. The independent variables examined are service quality and price, while the dependent variable is customer satisfaction with Gojek in Jakarta. The study population and sample consist of 96 Gojek users from Jakarta, selected through non-probability sampling using purposive sampling techniques. Sample criteria included Gojek service users residing in Jakarta, aged 17 or older, and who have utilized Gojek services in the past month. Data were gathered via questionnaire distribution and analyzed employing linear regression analysis. This study tested three hypotheses: (1) Service quality affects Gojek customer satisfaction in Jakarta; (2) Price influences Gojek customer satisfaction in Jakarta; (3) Both service quality and price together impact Gojek customer satisfaction in Jakarta. Findings reveal that both independent variables exert a positive and significant effect on customer satisfaction, both individually and collectively. The study concludes that enhancements in service quality and appropriate pricing strategies can improve customer satisfaction. The implications of these findings suggest that Gojek management should continue to prioritize improvements in service quality and pricing strategies to sustain and augment customer satisfaction in Jakarta.